Tax-Exempt Lobbying: Corporate Philanthropy as a Tool for Political Influence - Bertrand, Marianne; Bombardini, Matilde; Fisman, Raymond; Trebbi, Francesco (American Economic Review, 2020)
We explore the role of charitable giving as a means of political influence. For philanthropic foundations associated with large US corporations, we present three different identification strategies that consistently point to the use of corporate social responsibility in ways that parallel the strategic use of political action committee (PAC) spending. Our estimates imply that 6.3 percent of corporate charitable giving may be politically motivated, an amount 2.5 times larger than annual PAC contributions and 35 percent of federal lobbying. Absent of disclosure requirements, charitable giving may be a form of corporate political influence undetected by voters and subsidized by taxpayers. (JEL D22, D64, D72, L31)